PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK BERBASIS APLIKASI FLIP BUILDER PADA MATA PELAJARAN PPKN MATERI PENERAPAN PANCASILA DALAM KONTEKS BERBANGSA TERHADAP MEMOTIVASI BELAJAR SISWA - Lina Marlina (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2023)
ABSTRACT This study aims to motivate student learning in class XI MIPA 2 SMA Negeri 5 Kota Serang with a total of 30 students, while the object of this research is student motivation. the research method used is the Research And Development research method. The use of Pop Up Book teaching materials based on the Flip Builder application is used so that students can be motivated in learning, especially in PPKn subjects in the material for applying Pancasila in the context of the nation, the Flip Builder application pop up book is used so that PPKn teaching materials are more interesting and students don't feel bored when learning In class, PPKn subjects are a subject that discusses a lot about images about the nation and state, therefore PPKn requires explanations in the form of pictures and videos or animations so that students better understand PPKn subjects during class learning, to increase student learning motivation in When it comes to PPKn subjects, students must be given feedback so that learning has two-way communication and so that students can develop abilities in the classroom so that student learning is more motivated.